165k views
3 votes
The work of a student trying to solve the equation 4(2x − 1) = 11 + 3x + 5 is shown below:

Step 1: 4(2x − 1) = 11 + 3x + 5
Step 2: 8x − 4 = 16 + 3x
Step 3: 8x + 3x = 16 − 4
Step 4: 11x = 24
Step 5: x = 2.18

In which step did the student first make an error and what is the correct step?

Step 2: 8x − 1 = 16 + 3x
Step 2: 8x − 8 = 6 + 3x
Step 3: 8x − 3x = 16 + 4
Step 3: 8x + 3x = 16 − 8

In which step did the student first make an error and what is the correct step?

Step 2: 8x − 1 = 16 + 3x
Step 2: 8x − 8 = 6 + 3x
Step 3: 8x − 3x = 16 + 4
Step 3: 8x + 3x = 16 − 8

User Shampoo
by
5.8k points

2 Answers

4 votes

Answer: 8x -3x = 16+4

Explanation:

User Vegard Stikbakke
by
5.8k points
6 votes
Step 3: 8x -3x = 16+4
User Ratique
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.